Volatile fatty acids production from fermentation of waste activated sludge (2020)
The population growth has increased in the globe and, with it, the waste generation resulting in a severe problem. It is mandatory to assess production alternatives for the generation of bio-based products from residual sources. As is well known, plastic pollution is one of the main issues, one of the alternatives to overcome the unstoppable demand for this product are bioplastics derived from polymers of biological origin. One of the main steps for the synthesis of the biopolymers is the volatile fatty acids (VFA) production by anaerobic digestion of residual sources. Consequently, this work evaluates the production of VFA by anaerobic digestion of activated sludge from a municipal wastewater treatment plant. An experimental design was constructed to determine the conditions that favour the production of VFA. The design managed three independent variables: the organic load (6 gVS/L and 4 gVS/L), pH values of 9.0, 10.0 and 11.0, and a temperature of 25°C. The results of the study show that the activated sludge is suitable to produce VFA, due to the total concentration; also it may be used as carbon source for bio-polymers synthesis in future stages of the process. Alkaline conditions seem to boost the production of VFA, which was between 372 to 1600 mg COD/L.